Marginal abatement cost and carbon reduction potential assessment for energy-intensive Industries: Case studies in China - Suyang Zhou; Qiyu Chen; Wei Gu; Peng Xia; Bo Yuan; Gang Lu; Yingxiang Wang (Energy Strategy Reviews, 2025)
Energy-intensive industries play a critical role in achieving carbon reduction goals. This paper proposes a quantitative evaluation model for Marginal Abatement Costs (MACs) and carbon reduction potential, enabling scientific assessment of abatement costs and capabilities. Building on this model, a comprehensive assessment framework is further introduced, integrating both economic and environmental dimensions through novel indicators such as the baseline MAC and the carbon reduction index. Using 2022 data on carbon reduction technologies and industrial carbon emissions from China’s steel, cement, petrochemical, power, and coal industries, an empirical analysis is conducted. The results reveal clear differences in abatement capabilities across industries, offering valuable insights for developing targeted low-carbon transition strategies in energy-intensive industries.